Two new species of nematode parasites, Cucullanus epinepheli sp. n. (Cucullanidae) and Procamallanus (Spirocamallanus) sinespinis sp. n. (Camallanidae), from marine serranid and haemulid fishes off New Caledonia - Moravec, Frantisek; Justine, Jean-Lou (Folia parasitologica, 2017)
Based on light and scanning electron microscopical studies, two new species of parasitic nematodes are described from marine perciform fishes off New Caledonia: Cucullanus epinepheli sp. n. (Cucullanidae) from the intestine of the brownspotted grouper Epinephelus chlorostigma (Valenciennes) (Serranidae) and Procamallanus (Spirocamallanus) sinespinis sp. n. from the intestine of the silver grunt Pomadasys argenteus (Forsskål) (Haemulidae). Cucullanus epinepheli sp. n. differs from its congeners mainly in possessing a unique structure of the anterior, elevated cloacal lip with a large posterior outgrowth covering the cloacal aperture and in the presence of cervical alae and two small preanal papillae on the median dome-shaped precloacal elevation. This is the second known nominal species of this genus parasitising fishes of the family Serranidae and the second representative of Cucullanus Müller, 1777 recorded from fishes in New Caledonian waters. Procamallanus (Spirocamallanus) sinespinis sp. n. is mainly characterised by 10-12 spiral ridges in the buccal capsule, the presence of wide caudal alae, three pairs of pedunculate preanal papillae, two unequally long spicules (465-525 µm and 218-231 µm) and by the tail tip with a knob-like structure in the male, and the broad, rounded tail with a terminal digit-like protrusion without cuticular spikes in the female. This is the fifth nominal species of the subgenus Spirocamallanus Olsen, 1952 reported from fishes in New Caledonian waters.
Keywords: South Pacific; New Caledonia; nemoci ryb; střeva; Fish Diseases; ryby; helminth parasite; Intestines; Nová Kaledonie; Female; Nematoda; Microscopy, Electron, Scanning; infekce hlísticemi řádu Ascaridida; zvířata; Ascaridida; Epinephelus; Fishes; ženské pohlaví; Male; Seuratoidea; mikroskopie elektronová rastrovací; Ascaridida Infections; Pomadasys; Animals; Camallanoidea; mužské pohlaví